2021
DOI: 10.1371/journal.pone.0250579
|View full text |Cite
|
Sign up to set email alerts
|

Five genetic variants explain over 70% of hair coat pheomelanin intensity variation in purebred and mixed breed domestic dogs

Abstract: In mammals, the pigment molecule pheomelanin confers red and yellow color to hair, and the intensity of this coloration is caused by variation in the amount of pheomelanin. Domestic dogs exhibit a wide range of pheomelanin intensity, ranging from the white coat of the Samoyed to the deep red coat of the Irish Setter. While several genetic variants have been associated with specific coat intensity phenotypes in certain dog breeds, they do not explain the majority of phenotypic variation across breeds. In order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…We successfully replicated 17 published associations for physical traits other than size (table S10), including for genes MITF ( 14 ) with white spotting [ p = 2.89 × 10 −37 ; SNP effect size ( b ) = −0.78], FGF5 and RSPO2 ( 58 ) with coat length ( p = 5.46 × 10 −54 ; b = +0.37) and texture ( p = 6.35 × 10 −9 ; b = +0.11), USH2A ( 59 ) with roan and/or ticking ( p = 5.31 × 10 −16 ; b = +0.20), RUNX3 ( 60 ) with pheomelanin intensity ( p = 4.11 × 10 −8 ; b = −0.20), and the β-defensin region ( 61 63 ) with brindle coat patterns ( p = 2.50 × 10 −107 ; b = +0.35) (fig. S25, D to I, and data S16).…”
Section: Resultsmentioning
confidence: 99%
“…We successfully replicated 17 published associations for physical traits other than size (table S10), including for genes MITF ( 14 ) with white spotting [ p = 2.89 × 10 −37 ; SNP effect size ( b ) = −0.78], FGF5 and RSPO2 ( 58 ) with coat length ( p = 5.46 × 10 −54 ; b = +0.37) and texture ( p = 6.35 × 10 −9 ; b = +0.11), USH2A ( 59 ) with roan and/or ticking ( p = 5.31 × 10 −16 ; b = +0.20), RUNX3 ( 60 ) with pheomelanin intensity ( p = 4.11 × 10 −8 ; b = −0.20), and the β-defensin region ( 61 63 ) with brindle coat patterns ( p = 2.50 × 10 −107 ; b = +0.35) (fig. S25, D to I, and data S16).…”
Section: Resultsmentioning
confidence: 99%
“…Out of 47,095 total variants identified, 5,603 segregated by phenotype, including 4,834 SNV and 762 short indels. Variant effect prediction identified missense variants in 5 genes ( Table 2 ), including a previously reported variant in the SLC26A4 gene (chr18:12,910,382 T > C) that was associated with pheomelanin intensity across breeds ( Slavney et al 2021 ). While the 2 missense variants in ARMC10 and GSAP were predicted to be deleterious by both SIFT and Polyphen-2, none of the missense variants affected genes known to be involved in any pigment pathways.…”
Section: Resultsmentioning
confidence: 99%
“…While several genes involved in pheomelanin intensity have been identified across dog breeds, the single-breed GWAS presented in this study only identified the CFA18 locus as significant within the Poodle breed. One of the top SNVs was a missense variant in SLC26A4 which has previously been associated with pheomelanin intensity across dog breeds, where it was hypothesized to be the causative variant ( Slavney et al 2021 ). The researchers found that the CFA18 locus explained a relatively small % of the total variance in pheomelanin across dog breeds (adjusted R 2 = 0.047), whereas loci on CFA2 and CFA20 explained over 50% of the variance across breeds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2C ), within the acceptable range for today’s Siberian husky breed (53–60cm ( 8 )), and had a double layered coat ( 13 ) that was mostly black with only a little bit of white ( 14 ). He was homozygous for an allele conferring tan points ( 15 ) and one for blue eyes ( 16 ), but both were masked by his melanistic facial mask ( 17 ), and his predicted light-tan pigmentation ( 18 ) may have been indistinguishable from white. He carried neither the “wolf agouti” nor “Northern domino” patterns that are common in the Siberian husky and other sled dog breeds today ( 19 ).…”
mentioning
confidence: 99%